IMPLEMENTASI PROGRAM DISDUKCAPIL KELILING MENCETAK DOKUMEN KEPENDUDUKAN (CALING TANDUK) DALAM MENINGKATKAN PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KLUNGKUNG - Jayanti Sasmitha, Cokorda Istri Agung; Supriliyani, Ni Wayan; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2019)
ABSTRACT Klungkung regency is one of the regency ini Bali which has the lowest number of population. According to that fact, of course it must be easy to give the best demography service to all citizen. But, the fact shows that the range of people who own demography document is still low, which is caused by minimum accessibility toward demography administration service. Caling Tanduk program is an innovative program from Klungkung government ini order to improve public service ini klungkung regency. Through the innovation of Caling Tanduk program, Klungkung Government attains to create more efficient demographic administration service process. The result of this research is the implementation of Caling Tanduk program in Population and Civil Registry Service Klungkung Regency has ran quite well, but there were still some obstacles in implementing this program, such as the lack of professionalism of human resource which was involved in this research, the socialization was not spread evenly, and the lack of specific Standard Operating Procedure about Caling Tanduk Program Keywords: Implementation, Caling Tanduk Program, Demographic Document